Perlindungan Hukum Tembakau Lembutan Temanggung Sebagai Potensi Indikasi Geografis Menurut Undang-Undang No 20 Tahun 2016 - Setiawan Budi Santoso; Adhi Budi Susilo (Universitas Ngudi Waluyo, 2023)
Temanggung is the highest tobacco-producing city in Indonesia, with this level there are several processed tobacco products such as manufactured tobacco, srintil tobacco and soft tobacco. Lebutan tobacco is tobacco that is thinly sliced as the main ingredient for